FRGS 15–244–0485 Final Report: Novel Model on Leakage Current Mechanisms of Radiation Hard Silicon Carbide Schottky Diodes - Hasbullah, Nurul Fadzlin (2018)
The degradation of high-voltage commercial Silicon Carbide Schottky power diodes from ROHM Semiconductor Co., and CREE, Inc., under different doses ranging from 2 to 15MGy of high energy (3.0 MeV) electrons is successfully studied and reported. Current-voltage and capacitance-voltage characterization techniques have been used to investigate the impact of the irradiation on the ideality factor, saturation current, series resistance and Schottky barrier height. The results of both models show that the forward bias current decrease with increasing irradiation dose while the reverse bias current increase except for the diodes irradiated with 15MGy. However, the ideality factor of the forward current corresponding to all irradiation doses did not significantly change until the dose of 15MGy. The ideality factor values at pre-irradiation state are 1.026 and 1.01 increased to 1.2 and 1.8 after 15MGy for both ROHM and CREE devices respectively. It has also been observed that, for both models, the saturation current increased until irradiation dose of 5MGy then decreased after the 10MGy dose which leads to the opposing behavior observed in Schottky barrier height for every dose respectively. Subsequently, the series resistance showed a significant rise for both models and are interpreted as being due to the changes in the effective dopant density during irradiation. The capacitance for both models has reduced after irradiation, therefore, suggesting the effective donor concentrations have also decreased with increasing irradiation dose probably due to trapping effect by the defects induced during the irradiation.